Chlamydia infection and respiratory disorders - Kuznetsov, Sergii; Kucherenko, Olena; Zharkova, Tatyana; Kucherenko, Marina (Kharkiv National Medical University, 2014)
Chlamydia infection and respiratory disorders Kuznetcov S., Kucherenko O., Zharkova T., Kucherenko M. Summery. Three chlamydial organisms are pathogenic to humans: C.pneumoniae, C.psittaci, and C.trachomatis. Clinical picture of chlamidiosis determine by species of the microbe. Efficiency of the treatment depends on timely and adequate Chlamydia infection and respiratory disorders Kuznetcov S., Kucherenko O., Zharkova T., Kucherenko M. Summery. Three chlamydial organisms are pathogenic to humans: C.pneumoniae, C.psittaci, and C.trachomatis. Clinical picture of chlamidiosis determine by species of the microbe. Efficiency of the treatment depends on timely and adequate therapy.
Keywords: Chlamydia